Soybean Adaptation to Water Stress on Vegetative and Generative Phases - Andi Safitri Sacita; Tania June; I. Impron (Universitas Sembilanbelas November Kolaka, 2018)
Soybean is rich in protein and is one of the main sources of vegetable protein which essential in enhancing public nutrition. Climate change is the main trigger of the occurance of extreme weather events makes plants become more vulnerable to drought. Drought stress significantly affect the decline in soybean production, especially when it occurs during the reproductive phase. This research aimed to identify the response of soybean to water stress as a reference for determining the adaptive and tolerant varieties. The research was arranged in split-split plot design, with main plot was varieties (Dering and Argomulyo), the development phase (vegetative and generative phases) as the subplot, and water stress in the form of irrigation intervals (2, 5, and 10 days) as the sub-sub plots. The results showed that water stress during the vegetative phase has not statistically significant effect on soybean production. Soybean crop adapted to water stress by reducing the number of leaves, the leaf area, stomatal openings, as well as doing motion response by folding leaves. This crop adaptation mechanisms affecting the formation of dry matter quantity, seeds yield, water use efficiency, and radiation use efficiency